2023
DOI: 10.1038/s41378-023-00512-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of pattern quality in maskless plasmonic lithography via spatial loss modulation

Abstract: Plasmonic lithography, which uses the evanescent electromagnetic (EM) fields to generate image beyond the diffraction limit, has been successfully demonstrated as an alternative lithographic technology for creating sub-10 nm patterns. However, the obtained photoresist pattern contour in general exhibits a very poor fidelity due to the near-field optical proximity effect (OPE), which is far below the minimum requirement for nanofabrication. Understanding the near-field OPE formation mechanism is important to mi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…24,86 Growing nanofabrication methods are increasingly used to create operational nanostructures with nanoscale dimensions. 87–89 Maskless techniques like focused ion beam (FIB) 90 and electron beam lithography (EBL) 61,91 offer high resolution, while masked technologies like nanoimprint lithography 3 offer fast throughputs and scalability to large-area substrates. Recent experimental works demonstrate that TiN/GaN is grown by molecular beam epitaxy, 59 and electron beam lithography is used to prepare TiN 54 and GaN 92 nanostructure arrays for various applications.…”
Section: Resultsmentioning
confidence: 99%
“…24,86 Growing nanofabrication methods are increasingly used to create operational nanostructures with nanoscale dimensions. 87–89 Maskless techniques like focused ion beam (FIB) 90 and electron beam lithography (EBL) 61,91 offer high resolution, while masked technologies like nanoimprint lithography 3 offer fast throughputs and scalability to large-area substrates. Recent experimental works demonstrate that TiN/GaN is grown by molecular beam epitaxy, 59 and electron beam lithography is used to prepare TiN 54 and GaN 92 nanostructure arrays for various applications.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, previous works have shown that the assist sub-pixel can relax the shape complexity of the PSF and then play a role in compensating the feature error induced by the decaying characteristics of the evanescent field. 32,34 However, the obtained pattern features of the grayscale values really depend on many factors, primarily the aerial image intensity for each grayscale value, the photoresist contrast, the development time, and the initial PR thickness. Unfortunately, accurate general theoretical formulas for describing the nonlinear relationships between them are lacking.…”
Section: Grayscale Patterning Methodsmentioning
confidence: 99%
“… 33 The final pattern accuracy has also been effectively improved to over 90% using near-field optical proximity correction (OPC) methods on the basis of the evanescent nature of the SPWs. 32,34 Additionally, patterns with large aspect ratios have been achieved using a hybrid plasmonic waveguide exposure system to amplify the plasmonic optical evanescent field in the photoresist (PR) layer. 35 Almost all of the previously reported results show that the decay characteristics of the SPWs critically affect the final pattern features in plasmonic lithography, but their corresponding relation has not yet been intensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…This results in challenging fabrication processes that do not necessarily scale up to large areas well. To date, the fabrication process of these devices is restricted to photolithography with ultraviolet wavelengths [16], and electron beam/ion beam lithography [17]. Both techniques pose important limitations for larger scale access, so new ways must be found to fabricate and control the in-plane emitters.…”
Section: Introductionmentioning
confidence: 99%